2008
DOI: 10.1103/physreve.77.021504
|View full text |Cite
|
Sign up to set email alerts
|

Role of inertia in nonequilibrium steady states of sheared binary fluids

Abstract: We study numerically phase separation in a binary fluid subject to an applied shear flow in two dimensions, with full hydrodynamics. To do so, we introduce a mixed finite-differencing/spectral simulation technique, with a transformation to render trivial the implementation of Lees-Edwards sheared periodic boundary conditions. For systems with inertia, we reproduce the nonequilibrium steady states reported in a recent lattice Boltzmann study. The domain coarsening that would occur in zero shear is arrested by t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 50 publications
2
25
0
Order By: Relevance
“…Since eliminating the finite-size effects requires a large system size, we must ensure the typical domain size L ( L x, y . Most of the recent publications 15,16,18 about the non-equilibrium phase separation tune the system size between 512 and 1024, and it is found that the finite-size effects are under control with such a system size. In this study, all simulations are done for asymmetric quenches on a L x 3 L y = 1024 3 512 mesh.…”
Section: Length Scale Time Scale and Parameter Setsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since eliminating the finite-size effects requires a large system size, we must ensure the typical domain size L ( L x, y . Most of the recent publications 15,16,18 about the non-equilibrium phase separation tune the system size between 512 and 1024, and it is found that the finite-size effects are under control with such a system size. In this study, all simulations are done for asymmetric quenches on a L x 3 L y = 1024 3 512 mesh.…”
Section: Length Scale Time Scale and Parameter Setsmentioning
confidence: 99%
“…While under shear the system is no longer periodic and the morphology will in general be anisotropic, we define the length scales using a gradient statistic for f A across the simulation box. We define a symmetric matrix 16,18,35 …”
Section: Length Scale Time Scale and Parameter Setsmentioning
confidence: 99%
“…At each time step we update ϕ n → ϕ n+1 using Eq. (10) in two successive partial steps [29]. This allows to have a better numerical stability.…”
Section: The Scheme For the Convection-diffusion Equationmentioning
confidence: 99%
“…to characterize the long and short principal axes of the domain morphology using a gradient statistic for f A across the simulation box. They are the reciprocal eigenvalues of the symmetric matrix 1,17,24 …”
Section: Parameter Configurationmentioning
confidence: 99%
“…; _ g À3=4 using the Lattice Boltzmann approach. After that, Fielding 17 took a further research and found no evidence for nonequilibrium steady states in inertialess systems, which confirmed the irreplaceable role of inertia in nonequilibrium steady states.…”
Section: Introductionmentioning
confidence: 99%